2012
DOI: 10.1111/j.2047-2927.2012.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between anogenital distance and age

Abstract: SUMMARYIn humans, recent studies have correlated anogenital distance (AGD) in adult men to intrinsic testicular function. Although rodent studies suggest that AGD is determined in utero and remains constant in adult life, it is not certain if AGD remains constant across a man's adult life. We sought to determine if adult male AGD varies based on age. A cross-sectional study of men being evaluated at a men's health clinic. Anogenital distance (the distance from the posterior aspect of the scrotum to the anal ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 25 publications
3
20
1
Order By: Relevance
“…Basically, AGD has been shown to reflect the amount of androgens to which a fetus is exposed in early development; higher in utero androgen exposure results in longer and more masculine AGD. In males, AGD has been found to have similar values in people of different age groups, suggesting that AGD may provide a measure of genital development and function throughout human adult life …”
Section: Introductionmentioning
confidence: 94%
“…Basically, AGD has been shown to reflect the amount of androgens to which a fetus is exposed in early development; higher in utero androgen exposure results in longer and more masculine AGD. In males, AGD has been found to have similar values in people of different age groups, suggesting that AGD may provide a measure of genital development and function throughout human adult life …”
Section: Introductionmentioning
confidence: 94%
“…testosterone therapy). [11,24] However, newer reports does suggest some plasticity to AGD in adult life thus questioning this theoretical benefit. [25] It is uncertain why AGD is correlated with certain semen parameters (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…[8][9][10] As AGD seems to be constant across a man's adult life, the clinical utility of AGD has been suggested in studies of infertile men. [11] AGD is shorter in men with spermatogenic failure compared to genital duct obstruction in men presenting with azoospermia. [12] In addition, a retrospective examination of men undergoing varicocelectomy demonstrated that men with a longer AGD are more likely to benefit from varicocele repair implying possible clinical utility in patient counseling.…”
Section: Introductionmentioning
confidence: 99%
“…In the human, AGD in male newborns is approximately double that of female newborns. This difference remains significant until 24-30 months of life then decreases up to adulthood [9,10,13]. So far, no study has evaluated the contribution of the ultrasound assessment of AGD between 11 and 13 WG + 6 days (corresponding to the time of the first routine ultrasonography during pregnancy) to determine fetal sex.…”
Section: Introductionmentioning
confidence: 99%